ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA SEKOLAH DASAR PADA MATERI PERBANDINGAN DAN SKALA - Nadia Nabillah Putri; Salma Alvira; Indri Januari Nurjanah; Uum Umairoh; Deti Rostika (STKIP Subang, 2023)
Until now, mathematics is still considered difficult by most students. The most frequently encountered difficulty among elementary school students is material regarding comparisons and scales. The aim of this research is to determine the factors that cause students' learning difficulties in comparison and scale material, as well as to find out the appropriate learning model for this material. This research uses a literature study method by collecting various sources and several studies that have been conducted. The results of this research show that the ability to understand concepts, problem solving, accuracy and inappropriate learning models are one of the factors causing students' learning difficulties in this material. Efforts that can be used are implementing innovative learning models, cooperative learning using the snowball throwing method, and using interesting teaching materials such as scale dioramas and dora maps.